ANALISIS KESTABILAN MODEL MATEMATIKA JUMLAH PEROKOK PENGARUH KENAIKAN HARGA ROKOK DENGAN DINAMIKA AKAR KUADRAT - ZAI, FIDELIS NOFERTINUS; SEMBIRING, ARYL ZULDAUS; VANBASTEN, ARDINAL; NASUTION, ANGGI NOVITA; SINAGA, LASKER PANGARAPAN (E-Jurnal Matematika, 2020)
Consumption of cigarettes in large quantities by the public is one of the main concerns in every country because cigarettes contain harmful ingredients that can trigger various diseases .  This journal will explain the mathematical model of the number of smokers affected by rising prices of cigarettes with square root dynamics . The population  is divided into four, composed of potential smokers, occasionally smokers, heavy smokers, and ex-smokers . The results  of the model analysis are that there is a single point of smoker’s endemic equilibrium . If conditions are met, then the endemic equilibrium point of smokers will be asymptotically stable, and over a long period of time there will always be a spread of smokers.